Tunicates have a complex, highly dynamic TNF superfamily - Ignacio Marín (PLoS ONE, 2026)
Genes of the Tumor Necrosis Factor Superfamily (TNFSF) encode proteins with critical roles in cell signaling in animals, particularly in immunity and development. The evolution of the TNF superfamily remains poorly understood. This study demonstrates that tunicates possess a much more complex TNF superfamily than previously assumed. Some species have a large number of TNFSF genes, up to 14, due to frequent, independent tandem duplications. Significantly, this number exceeds that observed in many vertebrates (e.g., all characterized cyclostomes, as well as some birds and reptiles). As in vertebrates, the TNF superfamily of tunicates is capable of rapid evolutionary change. All 24 model tunicate species analyzed have different sets of TNFSF genes and even closely related species often have quite distinct TNF superfamilies. A comparison of tunicate and vertebrate data suggests that four TNFSF genes were present in the last common ancestor of both lineages. One of these genes was subsequently lost while the other three underwent independent duplications in early tunicate evolution. Six TNFSF genes were likely present in the common ancestor of all tunicates except perhaps appendicularians, for which data remain inconclusive. These results are consistent with the current model of how the TNFSF vertebrate genes emerged and evolved, except that whole-genome duplications played a significant role in expanding the family in vertebrates but not in tunicates. Transcription data obtained from Ciona intestinalis type A ( C. robusta ) indicate that several distantly related TNFSF genes share similar patterns of expression during development and in adults. Gene expression data are compatible with TNFSF genes having multiple roles, some of them in the innate immune system. Their involvement in immune defense may explain the rapid changes in TNFSF gene number observed in both tunicates and vertebrates.